The Development of Android-Based Anatomy Edutainment Instruction Materials - Irmawati, Farizha; Rezqi, Erfitra; Oktaviana, Ika (Department of Physical Education, Sport, Health and Recreation, 2017)
This study aims to produce teaching materials anatomy edutaiment-based android decent and effective in learning in Prodi Education Biology IKIP Budi Utomo Malang. Android-based teaching materials capable of supporting Anatomy learning with various features provided and will be more communicative and interesting to use in learning. This research is a development research using ADDIE model. Based on the validation results indicate that anatomy based edutainment and anatomy teaching materials in both categories with the validation score of material experts 89 and the validation of media experts 86.4, so it can be concluded that the teaching materials anatomy edutainment based android decent and valid for use in learning Anatomy Student Study Program Physical Education Health and Recreation IKIP Budi Utomo Malang.